Preparation of PET matrix gradient composite fiber membrane for coal mine and Study on the dust filtration-moisture permeability - Gang ZHOU; Zhuo XU; Liwei JIANG; Guanshuang CHEN; Yunlong MA; Rulin LIU; Yongmei WANG (Meitan xuebao)
Dust particles in humid-hot-dusty underground mine environment pose a great harm to the physical and mental health of the operators. Among them, fine particulate dust is easy to be inhaled and can reach the deep alveolar area of the respiratory tract, which is the main cause of occupational pneumoconiosis in coal mine industry. Herein, the electrospinning technology was used to regulate the structure of micro-nano fibrous medias. And a kind of composite medias with both highly efficient dust capture and enhanced moisture permeability were prepared by the layer upon layer of spinning method. Hydrophilic fibers were used to enhance the adsorption of water, hydrophobic fibers were used to avoid the production of capillary water in the medias. Meanwhile, the wettable diversion layers were added to construct the gradient polyethylene terephthalate (PET) based composite fibrous filter media, which might solve the difficult problems of preparation, poor skin affinity and insufficient comfort. In this study, using PET as substrate, hydroxylated graphene was added to enhance diffusion and electrostatic adsorption effects to capture dust. And polyvinyl pyrrolidone was selected to regulate the hydrophilic gradient and improve the moisture permeability. Microstructure characterization and performance detection showed that the fabricated fibrous membranes had micro-nano scale fiber diameter, excellent structural regularity and relatively smooth surface topography, exhibiting a good regulation of fiber diameter and morphology. Moreover, the distribution of surface elements and functional groups of each fiber membrane was consistent with its feature. Comparative experiments showed that the multi-layer composite membrane showed a better dust filtering performance, with a quality factor of 0.439 Pa−1, and pore size distribution between 2.15 and 4.61 µm. Meanwhile, the contact angle test showed that the multi-layer composite membrane had a gradual wetting gradient variation from super-hydrophilic (0°) to hydrophobic (135.2°), and the water vapor transmission arrived at 5434.325 g/m2·24 h, which was 1.37 and 2.04 times higher than that of the hydrophilic and hydrophobic membranes, respectively. In addition, the terahertz scanning imaging analysis method was used to carry out the quantitative analysis of liquid water inside of the fiber material. Moreover, based on the terahertz scanning imaging analysis method, the transport mechanism of water molecules in the fiber membrane was clarified. It could be concluded that the proposed multi-layer gradient fibrous filter medias will have broad application prospects in the area of respiratory protection in the humid-hot-dusty industrial/ mining environment, which could also provide a new approach for the resource utilization of wastes.